THE EFFECT OF EDUCATION SECTOR EXPENDITURE, HEALTH SECTOR EXPENDITURE AND ECONOMIC GROWTH ON POVERTY LEVEL IN TANA TORAJA - karadeng, Jimmy Alfian Bongga (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
Poor people’s survival ability are influenced by the quality of human resources that they have. The government expenditure of the education sector and the health sector is one form of government policy in order to improve the people's human resources and realize equitable economic growth so that the poverty level can be decreased. The purpose of this research is to know the influence of government expenditure especially on health sector and education sector on the level of poverty and the influence of economic growth to the level of poverty. This research is conducted in Tana Toraja Regency, South Sulawesi Province. The analyzed data is health and education sector expenditure, economic growth and poverty rate from 2006 to 2016 and using multiple regression analysis.From the analysis results, it is known that health sector expenditure has a significant negatively effect on the level of poverty, meaning that the higher health sector expenditure will further decrease the level of poverty. The expenditure of the education sector has no effect on the poverty level, meaning that the high level of education sector spending does not affect the poverty level. Economic growth has a significant negative effect on the level of poverty, meaning that the higher the economic growth of the community will further decrease the level of poverty.Keywords: health sector expenditure, education sector, economic growth, poverty